생성형 AI를 활용한 사회과 융합 프로그램 개발 및 적용: 환각과 비판적 사고를 중심으로 - 박성욱; 이용배; Seong-Wook Park; Yong-Bae Lee (미래기술융합논문지, 2025)
The rapid development of generative artificial intelligence (AI) has raised expectations for increased learning efficiency and resource distribution in education, but critical review of potential risks remains necessary. Some studies highlight low student interest and concerns regarding the adoption of new technology, emphasizing the importance of critical thinking skills. This study developed an educational program that integrates generative AI into social studies for fourth-grade elementary students and analyzed changes in AI literacy to confirm its educational effectiveness. The program measured students' progress in AI foundational knowledge, AI application skills, and attitudes toward AI, with statistical validation through surveys. The results showed that students' understanding of foundational AI knowledge significantly improved through the program, and both their AI application skills and critical attitudes toward AI also demonstrated statistically significant growth. In conclusion, the findings confirmed that an educational program utilizing generative AI can effectively enhance students' AI literacy. We hope this study serves as a reference for integrated education using generative AI in elementary schools, and future research needs to explore the possibility of expanding this program to various subjects and grade levels. 최근 생성형 AI의 발전은 교육에서 학습 효율성 증대와 자원 분배의 기대를 높이고 있지만 잠재적 위험에 대한 비판적 검토가 필요하다. 일부 연구는 학생들의 낮은 관심과 위험성이 검증되지 않은 AI기술 도입에 대한 우려를 제기하며 비판적 사고 능력의 중요성을 강조하고 있다. 본 연구는 초등학교 4학년 학생들을 대상으로 생성형 AI를 활용한 사회 교과와 융합한 교육 프로그램을 개발하고 적용한 뒤 AI 리터러시의 변화를 분석하여 교육적 효과를 확인하였다. 교육 프로그램은 AI 기초지식, AI 활용능력, 그리고 AI 태도 측면에서 학생들의 변화를 측정하였으며 설문을 통해 통계적 검정을 수행하였다. 학생들은 설계된 프로그램을 통해 AI 기초지식에 대한 이해도가 유의미하게 향상되었고 AI 활용능력과 AI에 대한 비판적 태도 또한 통계적으로 유의미한 성장을 보였다. 결론적으로 생성형 AI를 이용한 교육 프로그램이 학생들의 AI 리터러시 향상에 효과적임을 확인하였다. 본 연구가 초등학교 생성형 AI 융합교육의 참고자료가 되길 기대하며 향후 연구에서는 본 프로그램을 다양한 교과 및 학년으로 확장하는 가능성을 탐색할 필요가 있다.